Economic and legal aspects of the innovative activity of enterprises in the context of the digital economy - Markova, Olga Vladimirovna; Yevgenievna Listopad, Ekaterina; Shelygov, Aleksandr Vladimirovich; Fedorov, Alexander Grigorievich; Kiselevich, Igor Valentinovich (Nexo Revista Científica, 2021)
The article deals with the economic and legal aspects of the innovative activity of enterprises in the context of the digital economy. The authors have established that the innovative activity of enterprises includes also the development of artificial intelligence and robotics and that in the current conditions when creating and using artificial intelligence technologies, the issue of ensuring national security in the digital environment becomes extremely important. In this case, the strategic goal of ensuring information security is to protect the vital interests of the individual and society against internal and external threats associated with the application of information technologies for various purposes contrary to civil law. It is proved that innovations will increase the investment attractiveness of the business, maintain a balance of creative freedom and internal control measures, self-regulation in the field of digital technologies, and develop a unified legal framework in the economic space.